Early pastoral mobility and seasonality in Kenya assessed through stable isotope analysis. (May 2020) - Janzen, Anneke; Balasse, Marie; Ambrose, Stanley H.
Abstract: Eastern African pastoralists today depend on mobility to access seasonally available pastures for their livestock. Here, we evaluate the importance of mobility strategies for maintaining herds during the Pastoral Neolithic era in southern Kenya through stable isotope analysis. We use carbon and oxygen isotope ratios of sequentially sampled modern and archaeological cattle, sheep, and goat tooth enamel to reconstruct seasonal vertical mobility strategies of early pastoralists in the region from 3000 to 1200 years ago. An altitudinal transition from C4 grasses at low elevations to C3 grasses at higher elevations permits tracking vertical mobility in the Kenya Rift Valley. Results from eight Pastoral Neolithic sites from southern Kenya show that cattle, sheep, and goats were almost exclusively herded at low elevations throughout the year. Higher variability in carbon isotopes of caprines compared to cattle suggests that caprines had greater seasonal dietary flexibility. Oxygen isotopes were not consistently useful for identifying seasonal patterns: intra- and interannual variability in tropical precipitation and plant water isotopic composition are confounding factors. Archaeological contexts representing local foragers that adopted pastoralism show herding strategies similar to those from established pastoral sites. These results suggest that lower elevation savannas were productive enough to support pastoralism year-round during the Pastoral Neolithic era. Highlights: Carbon isotopes demonstrate that cattle were not herded to high elevations. Livestock from all sites were herded similarly, including sites occupied by hunter-gatherers that adopted herding. Oxygen isotopes are of limited use for tracking mobility and seasonality in Kenya.